PEMBUATAAN POJOK BACA SEBAGAI UPAYA PENINGKATAN LITERASI SISWA DALAM KEGIATAN KAMPUS MENGAJAR - Wanggai, Febe Fenny Irawati; Doi, Maksimilianus; Lalong, Melkianus Bernadin; Mbindi, Maria Noviyanti (LPPM Universitas Flores, 2025)
Literacy is one of the fundamental skills that every individual must possess to navigate challenges in the era of globalization. A person is considered to have literacy skills if they have mastered the basic language skills of reading and writing. Low interest in reading can cause limitations in obtaining, understanding, and processing information and knowledge, which continues to develop rapidly. As a result, individuals who lack a literacy culture will have difficulty keeping up with current developments in the fields of education, technology and other social aspects. As an effort to overcome this problem, we, as students at Teaching Campus 8, created a work program by building a Reading Corner as a means to increase students' interest and literacy skills at SD INPRES Ndetuwar. It is hoped that the existence of the Reading Corner can be an effective solution in fostering a culture of literacy at SD INPRES Ndetuwaru by providing a reading room that is comfortable, interesting and inspiring for students.